Optimizing the Role of Committees in School Facilities and Infrastructure Management - M, Siti Maisaroh; S, Rustan; Kaharuddin, Kaharuddin (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This research utilizes a qualitative approach to investigate the role of committees in infrastructure management at SDN 8 Salobulo, Palopo City. Adequate facilities and infrastructure are crucial for enhancing the quality of learning, but challenges related to coordination and management are often encountered. The study incorporates interviews, observations, and document analysis to explore (1) strategies employed by the committee in managing facilities and infrastructure, (2) specific actions taken by the committee, and (3) challenges encountered throughout the process. The findings indicate that enhanced communication, effective planning, and increased transparency have positively influenced the school's reputation, resulting in higher student enrollments and a more conducive learning environment. These results provide insights for other schools seeking to improve their infrastructure management to facilitate effective learning.